(3cJGH GjSbdGhS aj GdeWGdYs - (3GjSbdGhSs
(3ChdgG (B:s
(3GdebOeGJ EPG cGfJ ebGOjQ YOJgG RhL cebGOjQ GH , HO , OQ Qg` g` Q QM hgj eJJGdjI s
(3BNQgG (B:s
(3RhL heWGdYg eJJGdjI eJSGhjI GdRjGOGJ hPdc eG CQOfG Je cJGH GjSbdGhS ai GdeWGdY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1459s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs